Role of Green & King Index in the Diagnosis of Iron Deficiency with Microcytic Anemia - Ahmad, Rizwan Shafeeq (International Journal of Pathology, 2020)
Objective: This study was carried out to determine the diagnostic accuracy of Green and King Index which based upon simple hematological parameters is thus cheap and easily available for the diagnosis of iron deficiency anemia. Methods: It was a cross-sectional study carried out in Pediatrics ward of PAEC general hospital between 1st January 2014 to 30th June 2014. Using Nonprobability consecutive sampling, 70 children with microcytic (<70fl) anemia (<12 mg/dl) were selected and serum Ferritin measured using electrochemiluminescence immunoassay (ECLIA). The automated hematology analyzer was used to calculate G & K Index. A cut off value of below 80 percent of G & K Index was considered as indicative of iron deficiency anemia. Statistical analysis was performed using SPSS 20.0. Results: In this study, the mean age of the patients was 2.99± 2.69 years. There were 36(51.4%) male and 34 (48.6%) female patients. Among the 70 patients showing microcytic anemia serum, Ferritin was < 15ng/L in 40 of the patients and hence were positive for iron deficiency anemia, whereas 30 patients were negative for IDA.31 patients were detected positive by both Ferritin and G & K index. A total of 5 patients were diagnosed as positive on G & K index but were negative on serum Ferritin and there were 9 patients who were diagnosed as negative on G & K index but were positive on Serum Ferritin. The sensitivity and specificity of Green & King index were 77.5 and 83.33% respectively. Diagnostic accuracy was 51.4%. Conclusion: G & K index is a useful test for correctly identifying the majority of children with iron deficiency anemia.